3D Printability of Lysine-Modified Myofibrillar Protein Emulsions - Lin Liao; Zilan Feng; Yoon-Yen Yow; Yajie Song; Yuxiao Liu; Lixiang Qin; Xiaofei Wu; Zhisheng Pei; Changfeng Xue (Foods)
This study explores the potential of lysine (Lys) and tilapia myofibrillar protein (MP) composite particles in the formulation of highly inwardly directed emulsions (HIPEs). Infrared spectroscopy, potentiometric analysis, and molecular docking studies revealed that the interaction between Lys and MP is primarily governed by hydrogen bonding and electrostatic forces. The incorporation of Lys significantly influenced the particle size, secondary and tertiary structures, solubility, and turbidity of MP. Lys-MP-stabilized HIPEs can form highly stable denser self-supporting gel network structures. Rheological analysis of HIPEs stabilized by MP showed a low energy storage modulus (G’ 110.66 Pa) and water–oil separation, therefore preventing 3D printing. However, HIPEs stabilized by Lys (especially 1.5 wt%) significantly improved the energy storage modulus (G’ 1002.10 Pa), increased viscoelasticity and thixotropic recovery, and reduced droplet size (10.84 μm), facilitating the use of HIPE inks for 3D printing. Furthermore, HIPEs stabilized with 1.5 wt% Lys-MP demonstrated superior print accuracy (91.36%), resolution, and clarity in 3D printing applications. Overall, these findings offer a promising strategy for developing Lys-MP composite particle-stabilized HIPEs tailored for advanced 3D printing technologies.